Humanist Guillaume Budé's artful rhetoric: responding in kind to Utopia. Issue 2 (December 2017) - Frank, Andrea
Abstract : Guillaume Budé's prefatory letter to More's Utopia was prominently placed by Erasmus and More. Beneath the letter's disorienting qualities, Budé engages key ideas of Utopia, among them justice, law and lawyers, the "gadfly" of avarice and other sources of political discord, and Christianity and government. Budé's rhetoric is subtly evocative, particularly in his irony, juxtaposition, and wealth of classical allusions, through which he indicates education of citizens and engaging rhetoric are means toward right government, the pursuit of "Hagnopolis"—an Augustinian Holy City—and ultimately demonstrates the truth, impossibility, and importance of the Utopian isle. Abstract : La lettre liminaire de Guillaume Budé à More fut placée dans l' Utopie de façon proéminente par More et Erasme. Sous les qualités intrigantes de cette lettre, Budé aborde certaines idées clés de l' Utopie, dont la justice, la loi et les juristes, les "mouches du coche"' que sont l'avarice et autres sources de discorde politique, ainsi que le christianisme et la gouvernance. La rhétorique de Budé possède une force de suggestion subtile, surtout par son ironie, ses juxtapositions et la richesse de ses allusions classiques, L'auteur indique par ce moyen que l'éducation des citoyens et la belle rhétorique sont nécessaires à un bon gouvernement, puis recommande la recherche d'"Hagnopolis"—la Cité Sainte augustinienne, pour finalement démontrer à la fois la vérité, l'impossibilité et l'importance de l'île utopique.